The Roles of Human Resource Management in achieving School Effectiveness - Abolo, Evuarherhe Veronica (International Journal of Educational Management, 2021)
Every organisation to which the school is a part, need the human resources for goals actualisation. Human resource management in the school plays a significant role in the coordination of the assigned duties to personnel for the realisation of educational goals. The paper espoused the indispensable need of the school manager in bringing about school effectiveness through the human resource. Furthermore the various responsibility of the school manager in bringing about effective school through the management of the human resource were highlighted. The theoretical framework underpinning the study is based on the Resource- Based theory, the Reinforcement theory and the Adams Equity theory. The Resource- Based theory is founded on the premise that organisation is made up of resources and that the valuable and scarce ones lead to competitive advantage. The Reinforcement theory conjectures that management can affect the human resources in his care through the use of motivational indices of reinforcement, punishment, and extinction. In the same vein the Adam's Equity theory of motivation proposes that an employee remuneration has a direct effect on his performance. The theory advocates that all human resources be treated with fairness in the organisation. The Equi-Human Resource Reinforcement model was adopted to vividly represent the indispensable nature of adequate motivational tips on human resources in bringing effective school management. The paper concluded that it is the school management sole responsibility to develop and manage human resources through various managerial techniques.